Spatiotemporal response of aquatic native and nonnative taxa to wildfire disturbance in a desert stream network - Whitney, James E. (Kansas State University, 2014)
Many native freshwater animals are imperiled as a result of habitat alteration, species introductions and climate-moderated changes in disturbance regimes. Native conservation and nonnative species management could benefit from greater understanding of critical factors promoting or inhibiting native and nonnative success in the absence of human-caused ecosystem change. The objectives of this dissertation were to (1) explain spatiotemporal patterns of native and nonnative success, (2) describe native and nonnative response to uncharacteristic wildfire disturbance, and (3) test the hypothesis that wildfire disturbance has differential effects on native and nonnative species. This research was conducted across six sites in three reaches (tributary, canyon, and valley) of the unfragmented and largely-unmodified upper Gila River Basin of southwestern New Mexico. Secondary production was measured to quantify success of native and nonnative fishes prior to wildfires during 2008-2011. Native fish production was greater than nonnatives across a range of environmental conditions, although nonnative fish, tadpole, and crayfish production could approach or exceed that of native macroinvertebrates and fishes in canyon habitats, a warmwater tributary, or in valley sites, respectively. The second objective was accomplished by measuring biomass changes of a warmwater native and nonnative community during 2010-2013 before and after consecutive, uncharacteristic wildfires. Several native insect and fish taxa decreased after both wildfires, whereas nonnative decreases were most pronounced for salmonids and more limited for other taxa. Finally, effects of uncharacteristic wildfires followed by extreme flooding on metapopulations of native and nonnative fishes were contrasted during 2008-2013. Wildfire and flood disturbances increased extinction probabilities of all native fishes while leaving many nonnative fishes unaffected. These findings revealed a swinging pendulum of native and nonnative success, wherein wildfire disturbance resulted in a pendulum swing in favor of nonnatives. Ensuring the pendulum swings back in favor of natives will be facilitated by management activities that decrease wildfire size and intensity and maintain inherent ecosystem resilience.
Keywords: Stream ecology; Benthic macroinvertebrates; Native fish conservation; Wildfire; Invasive species; Metapopulation dynamics; Conservation Biology (0408); Ecology (0329); Environmental Sciences (0768)